Intruder localization wireless sensor network radar design with virtual reference tags - Abdullah, Hadi (2014)
This research designs a WSN (Wireless Sensor Network) algorithm for human intruder localization and path detection. There are two commonly used position estimation techniques in WSN, ToA (Time of Arrival) and RSSI (Received Signal Strength Indicator). In ToA the difference between arrivals of signal is estimated and based on this information position of target is calculated. This technique produces better results but in real time the cost of nodes used increases due to synchronization requirement. On the other hand RSSI technique requires no synchronization and can be considered as most simple and low cost technique but its accuracy is very low. To increase the accuracy of RSSI this research introduces VRTs (Virtual Reference Tags). VRTs are previously used in RFID (Radio Frequency Identification) system to provide reference to the system. Four reference nodes are used such that one acts as transmitting while three as receiving nodes. These nodes are placed at the edges of surveillance area. NS2 (Network Simulator 2) is used to design the WSN. The surveillance area of system is taken as 80X80 meters. Nine scenarios are checked with varying number of VRTs mapped over surveillance area. From the results it is observed that as the number of VRT is increased, accuracy of WSN radar also increases. But in actual implementation greater number of VRT can result in greater hardware requirement in terms of processor and high speed data storage. Since the proposed WSN radar is designed for human intruder localization, the WSN accuracy is kept to 0.2 meters. In simulation for a surveillance area of 80X80 meters to locate and track human intruder with 0.2 meter accuracy, 1721 VRTs are required to be virtually mapped over surveillance area. This research also presents a proposed design of WSN which can be used in vehicles as road safety feature providing assistance to driver. The WSN consists of three receivers, one on each side and one in front and the surveillance area around the vehicle is divided into levels which determine whether it is safe for driver to move towards that side. Driver alerting method is also presented using vehicle‟s steering wheel.